2013
DOI: 10.1615/int.j.uncertaintyquantification.2012004044
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Sensitivity of an Eddy Viscosity Model: Analysis, Computation and Its Application to Quantifying Model Reliability

Abstract: An eddy viscosity model can be used as a computationally tractable alternative to that of the Navier-Stokes equations. Model errors immediately become a concern when considering such an approach, and quantifying this error is essential to understanding and using model predictions within an engineering design process. In this paper, sensitivity analysis is presented for a subgrid eddy viscosity model with respect to variations of the eddy viscosity parameter. We demonstrate the analysis utilizing the sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sensitivity studies can be used with great effect to help quantify the reliability of such calculations. While [22] did not explore particular methods to directly quantify model reliability, examples can be found in [23,24]. One such technique is to quantify reliability by using the linear estimate, ||v h (0) − v h (χ)|| ≤ χ||s h || + O(χ 2 ).…”
Section: Determining Reliability Of Time-relaxation Models χ Through mentioning
confidence: 99%
“…Sensitivity studies can be used with great effect to help quantify the reliability of such calculations. While [22] did not explore particular methods to directly quantify model reliability, examples can be found in [23,24]. One such technique is to quantify reliability by using the linear estimate, ||v h (0) − v h (χ)|| ≤ χ||s h || + O(χ 2 ).…”
Section: Determining Reliability Of Time-relaxation Models χ Through mentioning
confidence: 99%
“…Further, these authors have showed a numerical study of the sensitivity of a fluid model known as time relaxation model with respect to variations of the time relaxation coefficient (Neda et al , 1999). (Pahlevani and Davis, 2013) have developed and analyzed a numerical method for simulating an eddy viscosity model and its corresponding sensitivity with respect to the eddy viscosity parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, there have been studies on the sensitivity of fluid flows in different aspects, [3,9,23,39,41,42]. Assessing model error that leads to uncertainty quantification is an important application of sensitivity analysis, see [35,40] for recent works in this direction. Defining the sensitivity of state variables in a physical system as derivatives of state varaibles with respect to the selected parameter, there are basically two methods of numerically calculating the sensitivities: Forward Finite Difference method (FFD) and Sensitivity Equation Method (SEM).…”
Section: Introductionmentioning
confidence: 99%